2013
DOI: 10.1155/2013/986273
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Defensin PaDef from Avocado Fruit (Persea americanavar.drymifolia) Expressed in Endothelial Cells againstEscherichia coliandStaphylococcus aureus

Abstract: Antimicrobial therapy is a useful tool to control infectious diseases in general and rising antibiotic resistant microorganisms in particular. Alternative strategies are desirable, and antimicrobial peptides (AMP) represent attractive control agents. Mexican avocado (Persea americana var. drymifolia) is used in traditional medicine; however, the AMP production has not been reported in this plant. We obtained a cDNA library from avocado fruit and clone PaDef was identified, which has a cDNA (249 bp) encoding a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…Additionally to this classification, several classes of plant AMPs can also be divided by properties, such as covalent bonding patterns, hydrophobicity, net charge, or molecular targets (Wang, 2015). Among several different plant AMP classes, in fruits it is possible to detect (I) defensins (Meyer et al, 1996; Guzmán-Rodríguez et al, 2013; Seo et al, 2014), (II) lipid transfer proteins (LTPs) (Zottich et al, 2011), (III) glycine rich protein (Pelegrini et al, 2008), (IV) 2S albumin (Pelegrini et al, 2006; Ribeiro et al, 2011), (V) snakin (Daneshmand et al, 2013), (VI) napin (Da Silva Dantas et al, 2014), and (VII) and other fruit AMPs (Table 1). …”
Section: Fruit Antimicrobial Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally to this classification, several classes of plant AMPs can also be divided by properties, such as covalent bonding patterns, hydrophobicity, net charge, or molecular targets (Wang, 2015). Among several different plant AMP classes, in fruits it is possible to detect (I) defensins (Meyer et al, 1996; Guzmán-Rodríguez et al, 2013; Seo et al, 2014), (II) lipid transfer proteins (LTPs) (Zottich et al, 2011), (III) glycine rich protein (Pelegrini et al, 2008), (IV) 2S albumin (Pelegrini et al, 2006; Ribeiro et al, 2011), (V) snakin (Daneshmand et al, 2013), (VI) napin (Da Silva Dantas et al, 2014), and (VII) and other fruit AMPs (Table 1). …”
Section: Fruit Antimicrobial Peptidesmentioning
confidence: 99%
“…), showed antibacterial activity against Gram-positive and negative bacteria. Pa Def should inhibit 67.43 and 78.08% of the viability of Escherichia coli and Staphylococcus aureus , respectively, in concentrations for 10 at 100 μg.mL −1 , but it did not show deleterious activity against Candida albicans (Guzmán-Rodríguez et al, 2013). The tomato defensin TPP3 has a lipid binding specific for phosphatidylinositol (4,5)-bisphosphate (PIP2) with which it forms a dimeric configuration complex that is critical for membrane permeabilization and inhibits hyphal growth of Fusarium graminearum (Baxter et al, 2015).…”
Section: Fruit Antimicrobial Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…PaDef used in this work corresponds to the mature region (ATCETPSKHFNGLCIRSSNCASVCHGEHFTDGRCQGVRRRCMCLKPC, 47 aa) (Genbank KC007441) [18], which was chemically synthesized and obtained from BIOMATIK. Prior to assays, PaDef (5 mg/ ml) disulfide bond formation was accomplished by air oxidation in dimethyl sulfoxide (20%) for 5 days at room temperature.…”
Section: Peptidementioning
confidence: 99%
“…drymifolia) and expressed it as a fusion protein in the endothelial cell line BVE-E6E7. We showed that the conditioned media from these cells have antimicrobial activity against Escherichia coli and Staphylococcus aureus, important pathogens affecting animals and humans [18]. However, its cytotoxic effect has not been explored.…”
Section: Introductionmentioning
confidence: 99%